Assessment of air quality in bus terminal stations in Eastern Province, Kingdom of Saudi Arabia - Salama, Khaled F.; Alhajri, Rashed F.; Al-Anazi, Abdulrahman A. (International Journal Of Community Medicine And Public Health, 2017)
Background: Bus terminal represent a significant air pollution problem. The use of diesel engines by public transport vehicles results in several air pollutants inside the bus termini. The major source of poor air quality includes industrial activities and traffic pollution that might have great deterioration impact upon the public health and surrounding environment. The main pollutant resulting from bus exhaust emissions are, by mass, carbon dioxide (CO2), Sulfur dioxide (SO2), nitrogen oxides (NOx), carbon monoxide (CO), particulate matter (PM), hydrocarbons (HC), volatile organic compounds (VOC) and BETEX (benzene, toluene, ethyl benzene and the three isomers of xylene). Bus fleets represent a significant part of inner city traffic. The present study aimed to assess air quality of bus terminal stations in Eastern Province of Saudi Arabia. Methods: This study was conducted at different bus terminal stations in Eastern Province. The location was chosen randomly. Air quality monitors were used for analyzing VOCs, CO, CO2, NO2, SO2 and O3 concentrations. BETEX and PM fractions were measured by applying infrared spectroscopy techniques and dust collection calibrated devices respectively. Results: Data of indoor and outdoor air pollution revealed that levels of NO2, SO2, CO, VOCs, PM10, PM4, PM2.5 and PM1.0 are higher than the permissible exposure limits and Saudi air quality guidelines in bus stations terminal in Dammam, Alhassa and Hafr Albatin bus stations garage, parking and waiting area in morning and noon time respectively. Conclusions: Ambient concentrations of gaseous and particulate air pollutants are above international guidelines at the different bus terminal sites in eastern provinces and these represent environmental and health risk for public and surrounding environment.